RELEVANSI ANTARA KEBUTUHAN KOMPETENSI KERJA ALUMNI DI INDUSTRI DENGAN MATERI YANG DIAJARKAN DI KELAS JURUSAN DPIB SMK NEGERI 1 GLAGAH BANYUWANGI - Pipy Ida Nur Khofifah; Sutrisno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The dynamics of the construction industry development require Vocational High School (SMK) graduates to have competencies relevant to the needs of the job market. This study aims to identify the level of competency needs in the industry, map the realization of teaching in schools, and analyze the suitability (gap) of work competencies of the Design of Building Modeling and Information (DPIB) graduates of SMK Negeri 1 Glagah. This research is a quantitative descriptive study using a survey method. The population and sample involved 30 alumni working in the construction industry and 30 twelfth-grade DPIB students. The data collection instrument used a Guttman-scale questionnaire. The results showed that basic and conventional competencies have been realized very well in schools and are in accordance with industry needs. However, there is a significant discrepancy (undersupply) in the mastery of state-of-the-art technology. The largest negative gap occurred in the operation of Total Station (-50.0%), BIM Modeling Revit (-46.7%), and Digital Data Processing / Mapping Software (-36.6%). Conversely, there is a very high oversupply in the Manual Drawing competency (+66.7%). Based on hypothesis testing using Chi-Square, 15 competencies were declared a match, while 8 crucial competencies experienced significant gaps. In conclusion, there is a sharp competency disparity between the learning achievements in schools and the digital transition required by the current construction industry.